2012
DOI: 10.1038/ejcn.2012.104
|View full text |Cite
|
Sign up to set email alerts
|

Increased intestinal permeability in malnourished patients with liver cirrhosis

Abstract: BACKGROUND/OBJECTIVE: Malnutrition is a prominent feature in liver cirrhosis, with deleterious impact on clinical outcome. The objective of this study is to investigate whether malnutrition is associated with increased gastrointestinal permeability in liver cirrhosis reflected by altered urinary excretion of non-metabolizable sugar probes. SUBJECTS/METHODS: Patients with advanced liver cirrhosis (Child Pugh Score B or C) were recruited. Nutritional status was determined according to the Subjective Global Asses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
41
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(44 citation statements)
references
References 35 publications
2
41
0
1
Order By: Relevance
“…Plasma Giardia-specific-IgM were only measured in the infants from Bangladesh, and occurred in 98% of them. PEW was also associated with decreased small bowel permeability (L:M ratio), in hospitalized adults [33] and patients with liver cirrhosis [51]. Interestingly, Hulsewe et al could not reproduce these results in 26 patients requiring preoperative total parenteral nutrition (TPN) [52].…”
Section: Function Of Gut Epithelium In Depleted Nutritional States Inmentioning
confidence: 96%
“…Plasma Giardia-specific-IgM were only measured in the infants from Bangladesh, and occurred in 98% of them. PEW was also associated with decreased small bowel permeability (L:M ratio), in hospitalized adults [33] and patients with liver cirrhosis [51]. Interestingly, Hulsewe et al could not reproduce these results in 26 patients requiring preoperative total parenteral nutrition (TPN) [52].…”
Section: Function Of Gut Epithelium In Depleted Nutritional States Inmentioning
confidence: 96%
“…Malnutrition is a commonly precipitating state among cirrhotic patients, and its prevalence might be even 80% [3]. Moreover, poor absorption (especially in patients with coexisting bile duct diseases) and increased gastrointestinal permeability are also involved [4]. In consequence, because of the deterioration in the storage of nutrients and altered hepatic synthesis, hypoalbuminemia occurs.…”
Section: Malnutrition In the Course Of Liver Cirrhosis And Methodsmentioning
confidence: 99%
“…In an Italian study, intestinal hyperpermeability has been shown to be more common in patients with a history of SBP [68]; in a Korean study, it was considered to be a predictor of bacterial infections in cirrhosis [75]. Four studies, 3 from the Western world (Spain, USA and Italy) and 1 from China [68,70,76,77], reported a significantly higher intestinal permeability in cirrhotic patients with ascites, although other studies did not observe a significant difference [67,69,73,78,79,80]. Contrasting results have been reported on the association between intestinal permeability and HE as well [67].…”
Section: Intestinal Hyperpermeabilitymentioning
confidence: 99%